Parental knowledge and usage of air quality in childhood asthma management - Reyes-Angel, Jessica; Han, Yueh-Ying; Forno, Erick; Celedón, Juan C; Rosser, Franziska J (Frontiers in Pediatrics, 2022)
Background: The current United States asthma management guidelines recommend usage of the Air Quality Index (AQI) for outdoor activity modification when air pollution is high. Little is known about parental knowledge and usage of air quality including the AQI in managing childhood asthma. Methods: Forty parents (or legal guardians) of children with persistent asthma completed a questionnaire designed to assess 4 areas related to outdoor air pollution: awareness, perception, behavioral modification, and prior healthcare provider discussion. Descriptive statistics were obtained and Fisher’s exact test was used for analysis of behavioral change by selected variables. Results: Almost all parents reported awareness of air quality alerts or AQI, however, only 20% checked the AQI on the AirNow app or website. Most parents reported air pollution as a trigger (65%), yet few parents reported behavioral modification of their child’s outdoor activity based on the perception of poor air quality (43%) or based on AQI or alerts (40%). Over half of parents reported a healthcare provider had ever discussed air pollution as a trigger, with few parents (23%) reporting recommendations for behavior change. Perception of air pollution as a trigger, healthcare provider discussion and recommendations, and usage of AirNow were associated with increased reported activity change. Conclusion: Healthcare providers should discuss outdoor air pollution during asthma management in children and should discuss AirNow as a source for AQI information and behavioral recommendations.